A Regression Analysis of Determinants Affecting Crude Oil Price - Alredany, Wajdi Hamza Dawod (International Journal of Energy Economics and Policy, 2018)
Studies and researches have been carried out on factors affecting crude oil prices; however, in most of these studies factors that have contributed to the fluctuation in oil prices, e.g. days of forward supply, convenience yield, underinvestment and geopolitics have been ignored. The importance of financial variables and geopolitics has also increased volume of transactions that would today represent about thirty-five times the oil traded in the physical market. This paper describes a new model of the most important variables that affect crude oil prices by using a new technique called principal component analysis (PCA) that can capture the Fundamental and geopolitical variables. Results indicate that fundamentals and the role of organization of petroleum exporting countries are the most important variables that affect crude oil prices. Keywords: Oil Price, Regression Analysis, Organization of Petroleum Exporting Countries JEL Classifications: E39, C13